The ambiguous other. Engaging with far right and other uncomfortable subjectivities - Katerina Hatzikidi (Vibrant: Virtual Brazilian Anthropology)
Abstract: This article explores anthropological hesitation in engaging with “abject” or otherwise “uncomfortable” subjectivities, identifying some of the main concerns and challenges behind it. In doing so, the discussion focuses on far-right subjectivities and on the reasons behind the relative lack of ethnographic studies thereof. Among other things, it is argued that the far-right other does not fit current anthropological orthodoxy in terms of ethnographic approach and therefore represents a kind of ambiguous alterity that poses ethical and methodological challenges for anthropologists. The discussion then brings to light some of the tensions and dilemmas inherent in anthropological approaches to uncomfortable alterities. The article concludes by highlighting what may be at stake for anthropology when excluding certain subjects of research, suggesting instead that their study offers opportunities to expand anthropological horizons of knowledge production, increasing the discipline’s relevance for understanding and analysing complex and troubling contemporary social phenomena.